2019
DOI: 10.1002/anie.201905922
|View full text |Cite
|
Sign up to set email alerts
|

An Acyclic Arsenium Cation Stabilised by a Single P–As π‐Interaction and a Cyclic Diphosphinophosphonium Salt

Abstract: Stable acyclic arsenium cations R2As+, isoelectronic analogues of germylenes, are rare in comparison to the corresponding phosphenium cations. The first example of a diphosphaarsenium salt, [{(Dipp)2P}2As][Al{OC(CF3)3}4]⋅11/2  PhMe, is described. This salt exhibits remarkable stability due to the delocalisation of a lone pair from a planar phosphorus centre into the vacant p‐orbital at arsenic; the bonding in 2 has been probed by DFT calculations. An attempt to synthesise an analogous diphosphaphosphenium salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Schulz et al reported on the synthesis of a 3-bisma-2-pentazenium cation [R 2 N-N­(R)-BiN­(R)-NR 2 ] + (R = (CH 3 ) 3 Si) . Izod et al isolated a phosphine-stabilized acyclic arsenium cation [{(Dipp) 2 P} 2 As]­[Al­{OC­(CF 3 ) 3 } 4 ] . In 2018, Beckmann et al reported two-coordinated stibenium and bismuthenium ions, [(2,6-Mes 2 C 6 H 3 ) 2 E]­[BArF 4 ] (E = Sb, Bi), obtained by using bulky meta -terphenyl substituents, which were heavier isoelectronic analogues of carbenes .…”
mentioning
confidence: 99%
“…Schulz et al reported on the synthesis of a 3-bisma-2-pentazenium cation [R 2 N-N­(R)-BiN­(R)-NR 2 ] + (R = (CH 3 ) 3 Si) . Izod et al isolated a phosphine-stabilized acyclic arsenium cation [{(Dipp) 2 P} 2 As]­[Al­{OC­(CF 3 ) 3 } 4 ] . In 2018, Beckmann et al reported two-coordinated stibenium and bismuthenium ions, [(2,6-Mes 2 C 6 H 3 ) 2 E]­[BArF 4 ] (E = Sb, Bi), obtained by using bulky meta -terphenyl substituents, which were heavier isoelectronic analogues of carbenes .…”
mentioning
confidence: 99%
“…A closely related bisphosphanylarsenium ion has been reported few years ago, whereas the corresponding phosphenium ion underwent rearrangement and could not be detected. 15 We have chosen the triphospha [3]ferrocenophane scaffold for our investigation which has been demonstrated to limit the number of isomers emerging from the stereogenic nature of the flanking phosphanyl units. 16 The analogous 1,3,2-diazaphospha- [3]ferrocenophane scaffold has already been successfully employed for isolation of a phosphenium ion I (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The first isolated and structurally characterized arsenium cations were reported by Burford in 1992, and although much rarer than phospheniums, a number of examples do exist . Although a lone pair and a vacant p ‐orbital are still present, their bonding to transition metals is typically confined to Lewis acid chemistry, where there is little to no σ‐donation from the lone pair .…”
Section: Introductionmentioning
confidence: 99%